Nucleic Acid Immunity and DNA Damage Response: New Friends and Old Foes - Taffoni, Clara; Steer, Alizée; Marines, Johanna; Chamma, Hanane; Vila, Isabelle K.; Laguette, Nadine (Frontiers in Immunology, 2021)
The maintenance of genomic stability in multicellular organisms relies on the DNA damage response (DDR). The DDR encompasses several interconnected pathways that cooperate to ensure the repair of genomic lesions. Besides their repair functions, several DDR proteins have emerged as involved in the onset of inflammatory responses. In particular, several actors of the DDR have been reported to elicit innate immune activation upon detection of cytosolic pathological nucleic acids. Conversely, pattern recognition receptors (PRRs), initially described as dedicated to the detection of cytosolic immune-stimulatory nucleic acids, have been found to regulate DDR. Thus, although initially described as operating in specific subcellular localizations, actors of the DDR and nucleic acid immune sensors may be involved in interconnected pathways, likely influencing the efficiency of one another. Within this mini review, we discuss evidences for the crosstalk between PRRs and actors of the DDR. For this purpose, we mainly focus on cyclic GMP-AMP (cGAMP) synthetase (cGAS) and Interferon Gamma Inducible Protein 16 (IFI16), as major PRRs involved in the detection of aberrant nucleic acid species, and components of the DNA-dependent protein kinase (DNA-PK) complex, involved in the repair of double strand breaks that were recently described to qualify as potential PRRs. Finally, we discuss how the crosstalk between DDR and nucleic acid-associated interferon responses cooperate for the fine-tuning of innate immune activation, and therefore dictate pathological outcomes. Understanding the molecular determinants of such cooperation will be paramount to the design of future therapeutic approaches.